2012
DOI: 10.1007/s10067-012-2152-8
|View full text |Cite
|
Sign up to set email alerts
|

Leflunomide-induced DRESS syndrome with renal involvement and vasculitis

Abstract: DRESS or drug reaction (or rash) with eosinophilia and systemic symptoms belongs to the severe cutaneous adverse reaction group and is characterized by hematological abnormalities and visceral organ involvement. Although most often related with anticonvulsant and sulfonamide use, it is reported with numerous other drugs. We report an unusual case of DRESS syndrome due to Leflunomide, also complicated by renal involvement in the form of granulomatous interstitial nephritis and vasculitis. On a review of the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
1
12
0
2
Order By: Relevance
“…Antibiotics-beta-lactams, sulfonamides, minocycline, ciprofloxacin [12], nitrofurantoin [13], azithromycin, linezolid [14] Antituberculosis medications-rifampin, amikacin [15,16] Proton pump inhibitors [17] Immunomodulators-cyclosporine, lenalidomide [18], leflunomide [19], dapsone, pentoxyphylline [20], sulfasalazine…”
Section: Risk Factorsmentioning
confidence: 99%
“…Antibiotics-beta-lactams, sulfonamides, minocycline, ciprofloxacin [12], nitrofurantoin [13], azithromycin, linezolid [14] Antituberculosis medications-rifampin, amikacin [15,16] Proton pump inhibitors [17] Immunomodulators-cyclosporine, lenalidomide [18], leflunomide [19], dapsone, pentoxyphylline [20], sulfasalazine…”
Section: Risk Factorsmentioning
confidence: 99%
“…13 While the liver is the most commonly implicated organ, kidney involvement has been reported in the form of acute tubulointerstitial nephritis with sulfasalazine and leflunomide. 14,15 Though the specific mechanistic link to renal failure is not clear, a recent study examining peripheral T-cell responses in 40 patients with DRESS found that a majority of cases involved human herpesvirus 6, human herpesvirus 7, and Epstein-Barr virus reactivation. 16 …”
mentioning
confidence: 99%
“…To our knowledge, there have been very few cases that have been presented similarly. [6][7][8] We believe that further investigation is required to explore the association between leflunomide and DRESS, so as to allow safe prescription and education of patients who require leflunomide.…”
Section: Discussionmentioning
confidence: 99%